Analisis Faktor Penyebab Terjadinya Kredit Macet - Andi Nursyahriana; Michael Hadjat; Irsan Tricahyadinata (FORUM EKONOMI, 2017)
This research aims to know the influence of debtors i.e. character of debtor, capacity, condition of economy, and collateral of debtor against non performing loans at PT Bank Tabungan Negara Cabang Bontang. This research was conducted in Bontang City. The methods used in this research was field survey by using questionnaire to 32 respondents in troubled debtor status. Sampling using cencus method. Data were analyzed by using multiple linear regression in statistical analysis with the help of the program SPSS ver. 20. Results of research conducted indicates that the variable character (X1) have significant and negative effect on non performing loans (Y), capacity (X2) have non significant and negative effect on non performing loans (Y), the variable condition of economy (X3) have non significant and negative effect on non performing loans (Y), and variable collateral (X4) have non significant and negative effect on non performing loans (Y).Keywords: non performing loan